Agenda Setting Rencana Pembangunan Jembatan Bangka-Sumatera: Agenda Setting for the Bangka-Sumatra Bridge Development Plan - Audia, Zilna Monika; Ibrahim, Ibrahim; Sarpin, Sarpin (Indonesian Democracy Research Center, 2023)
The research entitled